The Empowerment of Marginalized Community (Street Vendors) for Developing Creative Economy in Payakumbuh City West Sumatra - SYAMSIR, SYAMSIR (Jurnal Studi Pemerintahan, 2016)
This study generally aimed to find a model for empowerment of the marginalized community of street vendors for developing creative economy in Payakumbuh City, West Sumatra. While specifically this study aimed to get an overview of: 1) the City Government’s efforts in the empowerment of street vendors, and 2) the degree of success of the empowerment program of street vendors by the City Government. This study uses qualitative approach. Data collected through questionnaire, interview, observation, and documentation study in several government agencies and the street vendors in Payakumbuh, West Sumatra Province. Respondents in this study consisted of street vendors with business types of vegetables, fruits, accessories, foods, beverages, and other culinary merchants.Using frequency and percentage tests on responses by 445 respondents of street vendors and some informants in Payakumbuh city, West Sumatra, this study tested some aspects of marginalized community empowerment program Payakumbuh City. The findings of this study indicate that: 1) The empowerment of marginal urban communities (street vendors)by Payakumbuh Government has been running quite well; and 2) The level ofsuccess of the street vendors empowerment programs by the Payakumbuh Government during the time is still categorized as quite well, especially when it is measured based on capital movement of the street vendors.Keywords: Marginal Communities, Street Vendors (PKL), Community Empowerment, Capital Movement.